Expression of Functional Recombinant Human Tissue Transglutaminase (TG2) Using the Bac-to-Bac Baculovirus Expression System - Yaghoub Yazdani; Shahram Azari; Hamid Kalhor (Tabriz University of Medical Sciences, 2016)
Purpose: Tissue transglutaminase (TG2) is a unique multifunctional enzyme. The enzyme possesses enzymatic activities such as transamidation/crosslinking and non-enzymatic functions such as cell migration and signal transduction. TG2 has been shown to be involved in molecular mechanisms of cancers and several neurodegenerative diseases such as Alzheimer's disease. The present study aimed at cloning and expression of full length human TG2 in Bac-to-Bac baculovirus expression system and evaluation of its activity. Methods: pFastBac HTA donor vector containing coding sequence of human TG2 was constructed. The construct was transformed to DH10Bac for generating recombinant bacmid. The verified bacmid was transfected to insect cell line (Sf9). Expression of recombinant TG2 was examined by RT-PCR, SDS-PAGE and western blot analysis. Functional analysis was evaluated by fluorometric assay and gel electrophoresis. Results: Recombinant bacmid was verified by amplification of a band near to 4500 bp. Expression analysis showed that the enzyme was expressed as a protein with a molecular weight near 80 kDa. Western blot confirmed the presence of TG2 and the activity assays including flurometric assay indicated that the recombinant TG2 was functional. The electrophoresis assay conformed that the expressed TG2 was the indeed capable of crosslinking in the presence of physiological concentration calcium ions. Conclusion: Human TG2 was expressed efficiently in the active biological form in the Bac-to-Bac baculovirus expression system. The expressed enzyme could be used for medical diagnostic, or studies which aim at finding novel inhibitors of the enzymes . To best of our knowledge, this is probably the first report of expression of full length human tissue transglutaminase (TG2) using the Bac-to-Bac expression system.